Do online stock recommendations add value to Malaysian stock brokerage customers? / Lai Ming Ming and Lau Siok Hwa - Lai, Ming Ming; Lau, Siok Hwa (Accounting Research Institute (ARI) & Faculty of Accountancy, 2006)
This paper examines online buy, sell, and hold recommendations provided by brokerage analysts in post dot-com bubble burst in Malaysia which has created the Multimedia Super Corridor. The results reveal significant value added factor of the online recommendations on stocks' abnormal returns particularly on the release day. However, the very short-lived returns did not continue through the incorporation period. Quarterly results of the firms appear to be the most frequent rationale attributed for a recommendation made by the analysts. We suggest that brokerage customers capitalise on the advancement of information and communication technologies in their financial decisions making. For the financial services firms, the online services would be better integrated as part of the marketing strategies in enhancing customer satisfaction.